The Contribution of Self-Confidence and Emotional Intelligence Toward Students' Interpersonal Communication Anxiety and their Implications In Counseling and Counseling Services - Teri Santera; Neviyarni Neviyarni; Afdal Afdal (International Journal of Applied Counseling and Social Sciences, 2020)
This research aims to describe the contribution of self-confidence and emotional intelligence Toward Students' Interpersonal Communication Anxiety. This research uses a descriptive correlational quantitative method. The study sample was 100 students of the Senior High School Mahdaliyah Jambi City. This research uses a quantitative approach with descriptive methods. This study also uses a correlational method, with the analysis technique using simple regression and multiple regression which aims to test the contribution of two independent variables to one dependent variable. The variables in this study consisted of three, namely: self-confidence (X1) and emotional intelligence (X2) which were independent variables, and student interpersonal communication anxiety (Y) was the dependent variable. The results of this study indicate that self-confidence and emotional intelligence together have an effect on students' interpersonal communication anxiety by 164.5%. The implication of the results of this study can be used as a needs analysis in making the Guidance and Counseling service program at Senior High School Mahdaliyah Jambi City.